2022
DOI: 10.14814/phy2.15274
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnia elicits differential vascular and blood flow responses in the cerebral circulation and active skeletal muscles in exercising humans

Abstract: The purpose of this study was to investigate the effects of a rise in arterial carbon dioxide pressure (PaCO 2 ) on vascular and blood flow responses in the cerebral circulation and active skeletal muscles during dynamic exercise in humans. Thirteen healthy young adults (three women) participated in hypercapnia and normocapnia trials. In both trials, participants performed a two‐legged dynamic knee extension exercise at a constant workload that increased heart rate to roughly 100 beats m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 55 publications
0
5
1
Order By: Relevance
“…On a total of 163 eligible patients, we identi ed 23 (14%) patients who underwent moderate hypoventilation (PaCO 2 from 44 [42][43][44][45] to 50 [49-53] mmHg; p < 0.001) during the study period at a median of 6 (4-10) days following ICU admission; 6 patients had traumatic brain injury (TBI) and 17 had subarachnoid hemorrhage (SAH). A signi cant overall increase in median PbtO 2 values from baseline [21 (19-26) to 24 (22-26) mmHg; p = 0.02] was observed.…”
Section: Resultsmentioning
confidence: 99%
“…On a total of 163 eligible patients, we identi ed 23 (14%) patients who underwent moderate hypoventilation (PaCO 2 from 44 [42][43][44][45] to 50 [49-53] mmHg; p < 0.001) during the study period at a median of 6 (4-10) days following ICU admission; 6 patients had traumatic brain injury (TBI) and 17 had subarachnoid hemorrhage (SAH). A signi cant overall increase in median PbtO 2 values from baseline [21 (19-26) to 24 (22-26) mmHg; p = 0.02] was observed.…”
Section: Resultsmentioning
confidence: 99%
“…In 2022, targeted analyses were the most commonly applied approach for MS-based research in SES, with 52 human participant studies published. These experiments were predominantly performed in plasma 6,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] or serum, [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] with other biosamples mediums utilized such as urine, [51][52][53][54][55] fecal matter, 56,57 breath gases, [58][59][60][61][62][63] red blood cells, …”
Section: Targeted Analysismentioning
confidence: 99%
“…In 2022, targeted analyses were the most commonly applied approach for MS‐based research in SES, with 52 human participant studies published. These experiments were predominantly performed in plasma 6,16–35 or serum, 36–50 with other biosamples mediums utilized such as urine, 51–55 fecal matter, 56,57 breath gases, 58–63 red blood cells, 64 cerebrospinal fluid, 25 hair, 65 and whole blood via microsampling 66 . This excludes the use of IR and elemental MS to target specific isotope/elemental signatures, which are discussed individually within section 3.5.…”
Section: Analytical Approaches For Ms‐based Investigations In Ses In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Hypercapnia is considered organ-protective compared to hypocapnia [ 17 ], and in some cases, it is well tolerated in anesthetized patient [ 18 ]. Hypercapnia may lead to hemodynamic instability and may influence emergence from anesthesia [ 19 24 ]. The current evidence showed that compared with mechanical ventilation through an endotracheal tube, using THRIVE in short duration surgery was not associated with obvious intraoperative adverse events [ 3 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%